Abnormal cortical sources of resting state electroencephalographic rhythms in single treatment-naïve HIV individuals: A statistical z-score index. Issue 3 (March 2016) - Babiloni, Claudio; Pennica, Alfredo; Del Percio, Claudio; Noce, Giuseppe; Cordone, Susanna; Muratori, Chiara; Ferracuti, Stefano; Donato, Nicole; Di Campli, Francesco; Gianserra, Laura; Teti, Elisabetta; Aceti, Antonio; et al.
Highlights: This pilot study tested a statistical z -score procedure to identify single treatment-naïve HIV individuals having abnormal resting state electroencephalographic (EEG) sources. Compared to HIV individuals with normal EEG sources, those (47.6%) with abnormal z -score values showed worse cognitive and serological markers. This procedure is promising to assess effects of HIV on brain function in single treatment-naïve HIV individuals. Abstract: Objective: This study tested a simple statistical procedure to recognize single treatment-naïve HIV individuals having abnormal cortical sources of resting state delta (<4 Hz) and alpha (8–13 Hz) electroencephalographic (EEG) rhythms with reference to a control group of sex-, age-, and education-matched healthy individuals. Compared to the HIV individuals with a statistically normal EEG marker, those with abnormal values were expected to show worse cognitive status. Methods: Resting state eyes-closed EEG data were recorded in 82 treatment-naïve HIV (39.8 ys. ± 1.2 standard error mean, SE) and 59 age-matched cognitively healthy subjects (39 ys. ± 2.2 SE). Low-resolution brain electromagnetic tomography (LORETA) estimated delta and alpha sources in frontal, central, temporal, parietal, and occipital cortical regions. Results: Ratio of the activity of parietal delta and high-frequency alpha sources (EEG marker) showed the maximum difference between the healthy and the treatment-naïve HIV group. Z -score of the EEG marker was statistically abnormal in 47.6% of treatment-naïve HIV individuals with reference to the healthy group ( p < 0.05). Compared to the HIV individuals with a statistically normal EEG marker, those with abnormal values exhibited lower mini mental state evaluation (MMSE) score, higher CD4 count, and lower viral load ( p < 0.05). Conclusions: This statistical procedure permitted for the first time to identify single treatment-naïve HIV individuals having abnormal EEG activity. Significance: This procedure might enrich the detection and monitoring of effects of HIV on brain function in single treatment-naïve HIV individuals.